1987
DOI: 10.1172/jci112851
|View full text |Cite
|
Sign up to set email alerts
|

Dichloroacetate inhibits glycolysis and augments insulin-stimulated glycogen synthesis in rat muscle.

Abstract: The decrease in plasma lactate during dichloroacetate (DCA) treatment is attributed to stimulation of lactate oxidation. To determine whether DCA also inhibits lactate production, we measured glucose metabolism in muscles of fed and fasted rats incubated with DCA and insulin. DCA increased glucose-6-phosphate, an allosteric modifier of glycogen synthase, -50% and increased muscle glycogen synthesis and glycogen content > 25%. Lactate release fell; inhibition of glycolysis accounted for > 80% of the decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Our data are consistent with those of previous studies in isolated skeletal and cardiac muscles (6,10,11,27). Pearce and Connett (27) showed that 8 mM lactate resulted in profound decreases in insulin-stimulated glucose oxidation and lactate production in isolated soleus muscles.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our data are consistent with those of previous studies in isolated skeletal and cardiac muscles (6,10,11,27). Pearce and Connett (27) showed that 8 mM lactate resulted in profound decreases in insulin-stimulated glucose oxidation and lactate production in isolated soleus muscles.…”
Section: Discussionsupporting
confidence: 94%
“…Lactate was shown to decrease glycolysis, and thus its own production, in isolated rat skeletal muscle (6,27). In humans, lactate infusion inhibited endogenous lactate production (32).…”
mentioning
confidence: 99%
“…These findings are consistent with a reduction in fatty acid oxidation, increased glucose oxidation, and decreased lipolysis in DCAtreated animals. Plasma lactate concentrations were also reduced, consistent with an increased level of lactate oxidation and a reduction in skeletal muscle glycolysis 43 after DCA administration. The levels of ␤-hydroxybutyrate, which were elevated in the T3 animals relative to controls, were further increased in the DCA-treated animals.…”
Section: Effects Of Dichloroacetic Acid Treatment On the Hyperthyroidmentioning
confidence: 53%
“…Because of its known mechanism of action, high doses of DCA have been used clinically to treat lactic acidosis (36 -38) via lactate suppression, and it is also currently in clinical trials for the treatment of cancer (39 -41). In addition, DCA has been shown to stimulate glycogen synthesis in isolated primary hepatocytes (42) in the liver (43) and muscle (44) after oral administration and reported to stimulate insulin secretion and lower glucose concentration in the periphery after intracerebra ventricular administration (45), which is very similar to that of L-lactate (45). It is important to note that the concentration for DCA is often very high when administered in vivo (100 mg/kg to 1 g/kg) or used in the cell culture (1-10 mM), which suggests that the DCA concentrations might be sufficient to activate GPR81.…”
Section: Discussionmentioning
confidence: 99%